Noise energy harvesting in buckled BN nanoribbons from molecular dynamics. (July 2015) - López-Suárez, Miquel; Abadal, Gabriel; Gammaitoni, Luca; Rurali, Riccardo
Abstract: We present molecular dynamics calculations of a h -BN nanoribbon designed for vibrational energy harvesting. We calculate the piezoelectric voltage generated at the ends of the device as a function of time and for different levels of an external compressive strain. Through the full atomistic description of the nanoribbon dynamics we demonstrate that driving the system into a non-linear dynamical regime greatly increases its harvesting efficiency. A comparative analysis of the piezo-voltage dependence on the compressive strain, obtained from a previously reported description of the nanoribbon dynamics and from the more accurate molecular dynamics, reveals that the method here presented gives a more precise description of the effect of in-plane vibration of the atoms on the harvesting performance of the device. Graphical abstract: Highlights: We have studied the dynamics of a h-BN armchair nanoribbon as a function of an applied compressive strain for energy harvesting applications by means of atomistic molecular dynamics calculations. This is a simple and compact design for nanoscale ambient vibration harvesting, as the mechanical oscillator operates simultaneously as a piezoelectric transducer. Our calculations show that engineered non-linearities greatly increase the device performances in terms of harvested power, which can be as high as 8 pW. Importantly, the unification of the mechanical and the electromechanical transducer elements in one single material structure not only simplifies a possible fabrication process, but also broadens the range of compression that increases the device performance.